Incidence and risk factors for myocardial injury after laparoscopic adrenalectomy for pheochromocytoma: A retrospective cohort study - Lan, Ling; Shu, Qian; Yu, Chunhua; Pei, Lijian; Zhang, Yuelun; Xu, Li; Huang, Yuguang (Frontiers in Oncology, 2022)
Abstract Background: Pheochromocytoma is a rare catecholamine-secreting tumor. Tumor resection remains a high-risk procedure due to intraoperative hemodynamic instability nowadays, which may lead to myocardial injury. We aimed to determine the incidence and associated risk factors for myocardial injury after laparoscopic adrenalectomy for pheochromocytoma. Methods: Adult patients (n=350, American Society of Anesthesiology physical status 1–3) who underwent elective laparoscopic adrenalectomy for pheochromocytoma under general anesthesia between January 31, 2013 and January 31, 2020 were included in this observational, retrospective, single-center, cohort study. Blood troponin I levels were measured before and within 2 days after surgery. Myocardial injury was defined as an elevated troponin I level exceeding the 99th percentile upper reference limit due to cardiac ischemic causes. Results: Myocardial injury occurred in 42/350 patients (12.0%, 95% confidence interval: 9.0%–15.9%). In multivariable analysis (adjusted odds ratios [95% confidence intervals]), previous cardiovascular or cerebrovascular disease (5.04 [1.40–18.08]; P=0.013), intraoperative heart rate >115 bpm (2.55 [1.06–6.12]; P=0.036), intraoperative systolic blood pressure >210 mmHg (2.38 [1.00–5.66]; P=0.049), and perioperative decrease in hemoglobin level(1.74 [1.15–2.64] per g/dL decrease; P=0.008) were associated with an increased risk of myocardial injury. For the cumulative duration of dichotomized intraoperative hemodynamics, multivariable analysis showed that intraoperative heart rate >115 bpm for >1 minute (2.67 [1.08–6.60]; P=0.034) and systolic blood pressure >210 mmHg for >1 minute (3.78 [1.47–9.73]; P=0.006) were associated with an increased risk of myocardial injury. The risk of myocardial injury progressively increased with a longer cumulative duration of intraoperative tachycardia and hypertension. Conclusions: There is a high incidence of myocardial injury after laparoscopic adrenalectomy for pheochromocytoma. The identified risk factors may assist physicians in detecting high-risk patients and providing guidance for intraoperative hemodynamics and perioperative hemoglobin management.